2009
DOI: 10.1016/j.bcp.2009.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity and cellular processing in human ovarian carcinoma cell lines of a new platinum(II) compound containing a fluorescent substituted propylene diamine ligand

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Indeed, oxaliplatin as a single agent or in combination with other agents in ovarian cancer demonstrated minimal cross-resistance with cisplatin or carboplatin,37 while simultaneously showing some therapeutic activity in recurrent ovarian cancer 38. In our analyses of clinical trials, oxaliplatin combined with gemcitabine showed similar response rates to cisplatin combined with gemcitabine (28.7 vs. 21.7%, p=0.37); however, many on-going pre-clinical studies are actively investigating new synthetic platinum compounds that may have future clinical applications 3940…”
Section: Approaches For Treating Platinum Resistancementioning
confidence: 87%
“…Indeed, oxaliplatin as a single agent or in combination with other agents in ovarian cancer demonstrated minimal cross-resistance with cisplatin or carboplatin,37 while simultaneously showing some therapeutic activity in recurrent ovarian cancer 38. In our analyses of clinical trials, oxaliplatin combined with gemcitabine showed similar response rates to cisplatin combined with gemcitabine (28.7 vs. 21.7%, p=0.37); however, many on-going pre-clinical studies are actively investigating new synthetic platinum compounds that may have future clinical applications 3940…”
Section: Approaches For Treating Platinum Resistancementioning
confidence: 87%
“…To obtain the antiproliferative data with CloneSelect Imager and MTT from the same plate at the same time point the treated microtiter plates were first monitored using CloneSelect Imager system and subsequently 50 μL of a MTT solution (5 mg/ml in PBS buffer) were added to each well, and the plate kept at 37°C for 3 h to allow formation of the formazan crystals [1]. The solution was then carefully removed and the blue formazan crystals were dissolved in 100 μL DMSO, and the absorbance was read at 590 nm using an automatic microplate reader (Labsystems Multiskan MS) as previously described [20,21]. In the case of the mice leukemia cells, the plates were imaged with the CSI system.…”
Section: Methodsmentioning
confidence: 99%
“…Many efforts have been dedicated to explain the factors related to the anticancer activity of cisplatin and different platinum compounds [1,2] and although the molecular mechanistic studies of cisplatin and analogs have been largely developed, the cellular response to these compounds is still poorly understood [3,4].…”
Section: Introductionmentioning
confidence: 99%